2004
DOI: 10.1063/1.1710713
|View full text |Cite
|
Sign up to set email alerts
|

Visible light emission from polymer-based field-effect transistors

Abstract: Articles you may be interested inEffect of metal-polymer interface on the breakdown electric field of poly(vinylidene fluoride-trifluoroethylenechlorofluoroethylene) terpolymer Appl. Phys. Lett. 91, 062907 (2007); 10.1063/1.2768205 Lateral organic light-emitting diode with field-effect transistor characteristics J. Appl. Phys. 98, 074506 (2005); 10.1063/1.2060932 Nonlinear charge injection in organic field-effect transistors J. Appl. Phys. 97, 064508 (2005); 10.1063/1.1858874 Ambipolar organic field-effect tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 14 publications
0
64
0
1
Order By: Relevance
“…The controlled fabrication of highly periodic metal, [1] semiconductor, [2,3] or molecular [4] nanostructures at surfaces remains, however, a challenging endeavor in nanoscience research. Large quantities of structures can be created in parallel by self-organized growth, either in the kinetic, [5] or thermodynamic regime, [2,3,6] and deposition of size-selected clusters from the gas phase.…”
Section: Doi: 101002/adma200500913mentioning
confidence: 99%
See 1 more Smart Citation
“…The controlled fabrication of highly periodic metal, [1] semiconductor, [2,3] or molecular [4] nanostructures at surfaces remains, however, a challenging endeavor in nanoscience research. Large quantities of structures can be created in parallel by self-organized growth, either in the kinetic, [5] or thermodynamic regime, [2,3,6] and deposition of size-selected clusters from the gas phase.…”
Section: Doi: 101002/adma200500913mentioning
confidence: 99%
“…Polymerbased OLETs, where the active layer has been processed by spin coating, have been obtained from poly(9,9-diethylhexylfluorene) [3] and poly[2-methoxy-5-(2′-ethylhexyloxy)-1,4-phenylenevinylene]. [4] A co-evaporated layer of a-quinquethiophene (T5) and N,N-8-ditridecylperylene-3,4,9,10-tetracarboxylic diimide (P13) has been used to produce the first ambipolar OLET.…”
mentioning
confidence: 99%
“…The gate bias controls the location of the light emission (135,129) . In these light emitting FETs, high performance is obtained from the simultaneous injection of holes from the drain and electrons from the source (129) .…”
Section: All-polymer Fetsmentioning
confidence: 99%
“…In the same year, Omayada et al showed also a new single layer unipolar OLET with an EQE of almost 0.8%, made with a blend of 1wt%-rubrene doped tetraphenylpyrene (TPPy) (Omayada et al, 2005b). Other studies have been done using spin-coated or drop-casted polymers like polyphenylenevinylene, poly-fluorene or poly-arylenevinylene derivatives (Sakanoue et al, 2004;Ahles et al, 2004;Swensen et al, 2005a) as active layer. These experiments, besides showing a possible extension of the concept of unipolar OLET, demonstrated the feasibility of wet-technique fabrication process that could open up many possibilities of large-area and low cost devices.…”
Section: Unipolar Oletsmentioning
confidence: 99%